Effects of single-leg foot-landing techniques on ground reaction force and electromyography - Bai, Jinhao (2014)
Anterior Cruciate Ligament (ACL) injury has deleterious consequences on athletes both psychologically and financially. As the worldwide prevalence of ACL injury remains high today, developing prevention strategies is essential. The study aimed to examine the effects of foot-landing techniques on vertical ground reaction force (vGRF) and electromyographic (EMG) activities of the lower extremity during single-leg drop-landings. It was hypothesized that forefoot landing would result in lower vGRF and higher muscular activities of medial gastrocnemius (MG) and soleus as compared with flat-foot landing. Fifteen male basketball athletes (age = 23.6 ± 1.9 years, height = 175.4 ± 8.0 cm, mass = 68.4 ± 10.0 kg) with no previous surgery and existing injury on the lower extremity were each tasked to perform single-leg drop-landings from a 30 cm platform onto a force plate using three different foot techniques (self-preferred, forefoot, flat-foot). Kinematics, vGRF and EMG data were recorded. Values of EMG were separated into two sets of averaged data (landing phase, pre-landing phase). Flat-foot landing produced a significantly higher peak vGRF compared to self-preferred and flat-foot landings (p < .001). There were significant main effects in MG between different foot-landing techniques (p = .002) and between different phases of landing (p = .037). Significant interactions were observed between foot-landing technique and phase of landing in MG (p = .035), as well as in soleus (p = .031). These results demonstrate that forefoot landing technique can effectively activate calf muscles and lower vGRF, hence mitigating the possible risk of non-contact ACL injury.